THE AMBIVALENCE AND SOCIAL ENFORCEMENT OF WIDOWER ‘IDDAH NORMS IN MADURA - Abdul Azis; Zaenul Mahmudi; Abbas Arfan (JURNAL HAKAM, 2026)
This article examines the socio-legal construction of widower's iddah in Madura from an Islamic law perspective. It focuses on how widower mourning, although not formally codified in detail in the Kompilasi Hukum Islam, becomes a socially recognized and enforced norm in local Muslim communities. The study aims to analyze the ambivalence and social enforcement of widower's iddah and to assess whether it constitutes a legitimate expression of ‘urf and living fiqh or an excessive form of communal moral control. This research employed an empirical socio-legal design with a qualitative case study approach in Banyuates and Ketapang, Sampang Regency. Data were collected through in-depth interviews, observation, and field notes with 42 informants, including widowers, younger and older community members, religious leaders, and community leaders. The findings show that a widower's iddah functions as a morally binding norm shaped by kinship relations, communal morality, and local religious reasoning. Its enforcement is supported by Madurese values such as tengka, malo, todus, and ajhina abhâ’, as well as informal sanctions such as gossip, labeling, distancing, and reputational pressure. The study concludes that a widower's iddah may be accepted as a valid ‘urf only when it remains proportional, ethical, and consistent with maqāṣid al-sharī‘ah; otherwise, it risks becoming unjustifiable social coercion. Its legitimacy collapses when social enforcement turns that framework into excessive communal control that negates the widower’s legally permissible right to remarry.Keywords : widower ‘iddah, living fiqh, ‘urf, Madura, Islamic family law